Structural optimization method of rice precision direct seed-metering device based on multi-index orthogonal experimental - Li, Hanqing; Ling, Lin; Wen, Changkai; Liu, Huaiyu; Wu, Guangwei; An, Xiaofei; Meng, Zhijun; Yan, Bingxin (Frontiers in Plant Science, 2023)
The creation of a novel type of direct seed metering device is critical for increasing rice planting mechanization. The device's structural properties will be crucial in determining its seeding performance. Structure optimization in the current seed metering device design process focuses on a single or few indexes, resulting in improved individual performance but imbalanced overall performance. Therefore, a structure optimization method of the direct seeding device based on a multi-index orthogonal experiment was proposed in this study. First, the DEM-MBD coupling method observed the factors and levels that affected the performance overall. Second, a test platform based on the electric drive control model was constructed, and a multi-index orthogonal test was devised. Finally, the structural parameters of the seed metering devices were optimized based on matrix analysis. From the results, the primary and secondary levels of significance of factors were just as follows: hole diameterhole number > adjustment angle. The following are the optimal parameters found by optimization analysis: the diameter of the hole was 12 mm, the number of holes was 10, and the adjustment angle was 80°. Validation tests were carried out and analyzed based on the optimal structural parameter combination. The qualification rate of seeds per hole, empty hole rate, average seed number, coefficient of variation of seed number, average hole spacing, and the variance coefficient of hole spacing are 93.07%, 0%, 9.39,14.04%, 22.84 mm, and 9.14%, respectively. In comparison to traditional design and structural parameter optimization methods for rice precision seed metering device, this study not just to provides an optimization scheme for improving the overall performance of rice precision seed metering device, but also serves as a technical reference for the development and design of new rice precision seed metering device.